Measurement of the Λ+c to D0 production ratio in peripheral PbPb collisions at √sNN = 5.02 TeV - Aaij, Roel; Bachmann, Sebastian; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Leverington, Blake; Marks, Jörg; Unverzagt, Daniel Joachim; et al. (Journal of high energy physics, 2023)
We report on a measurement of the Λ+c to D0 production ratio in peripheral PbPb collisions at √sNN = 5.02 TeV with the LHCb detector in the forward rapidity region 2 < y < 4.5. The Λ+c (D0) hadrons are reconstructed via the decay channel Λ+c → pK−π+ (D0 → K−π+) for 2 < pT < 8 GeV/c and in the centrality range of about 65-90%. The results show no significant dependence on pT, y or the mean number of participating nucleons. They are also consistent with similar measurements obtained by the LHCb collaboration in pPb and Pbp collisions at √sNN = 5.02 TeV. The data agree well with predictions from PYTHIA in pp collisions at √s = 5 TeV but are in tension with predictions of the Statistical Hadronization model.
Im Text ist "+" und "0" hochgestellt, "c" tiefgestellt
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
The LHCb collaboration: R. Aaij, S. Bachmann, M. Borsato, R. Caspary, G. Frau, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, B. Leverington, J. Marks, D.J. Unverzagt, U. Uwer, L. Witola, A. Zhelezov [und viele weitere]
Gesehen am 27.10.2023